. Changes in Inflammatory Factors (IL-6, IL-10, IL-1β, and TNF-α) and Their Correlation with miRNAs Expression in Patients Undergoing Percutaneous Coronary Intervention: Correlation between Inflammatory Factors and miRNAs after PCI - Zeng, Shuai (Journal of Medical Biochemistry, 2026)
Background: Percutaneous coronary intervention (PCI) can induce vascular injury and inflammatory responses. miRNAs are involved in vascular homeostasis and repair processes, but their interactions with inflammatory factors after PCI are not yet fully defined. Objectives: The objective of this study was to determine the changes in inflammatory factors in PCI patients and their correlation with the expression of specific miRNAs. Methods: Patients undergoing PCI were selected as the observation group (AG), and healthy individuals undergoing physical examinations as the control group (BG). Inflammatory factors in the serumwere quantified adopting ELISA. RT-qPCR was utilized for measurement to assess the associations between inflammatory factors and miRNAs expression. Results: IL-6, IL-10, IL-1β, and TNF-α were markedly elevated in the AG versus the BG; in the AG, the expression of miRNA-21 was significantly up-regulated, while the expression of miRNA-92a and miRNA-126 was significantly down-regulated (P < 0.05). Correlation analysis showed that the levels of IL-6, IL-10, IL-1β, and TNF-α were positively correlated with the expression of miRNA-21 and negatively correlated with the expression of miRNA-92a and miRNA-126. Conclusion: Inflammatory responses are significantly activated in patients after PCI, accompanied by changes in miRNA expression profiles. Pro-inflammatory factors are positively associated with miRNA-21 and negatively associated with miRNA-92a and miRNA-126, reflecting their joint involvement in the damage and repair of blood vessels after surgery.